Joubert Syndrome Presenting with Motor Delay and Oculomotor Apraxia - Harjinder Gill; Brinda Muthusamy; Denize Atan; Cathy Williams; Matthew Ellis (Hindawi Limited, 2011)
We describe two sisters who presented in early childhood with motor delay and unusual eye movements. Both demonstrated hypotonia and poor visual attention. The older girl at 14 weeks of age showed fine pendular horizontal nystagmus more pronounced on lateral gaze, but despite investigation with cranial MRI no diagnosis was reached. The birth of her younger sister four years later with a similar presentation triggered review of the sisters' visual behaviour. Each had developed an unusual but similar form of oculomotor apraxia (OMA) with head thrusts to maintain fixation rather than to change fixation. MRI of the older sibling demonstrated the characteristic "molar tooth sign" (MTS) of Joubert syndrome which was subsequently confirmed on MRI in the younger sibling. We discuss the genetically heterogeneous ciliopathies now grouped as Joubert syndrome and Related Disorders. Clinicians need to consider this group of disorders when faced with unusual eye movements in the developmentally delayed child.